Evaluation of Cell Wall Yeast as Adsorbent of chratoxin in Broilers Diets - Santin, E. (International Journal of Poultry Science, 2003)
This study aimed to evaluate the efficacy of cell wall of Saccharomyces cerevisiae (CWSC) as an inhibitor of the toxic effects of ochratoxin in broilers from 1 to 42 days of age. A total of 320 broilers was distributed into four treatments with four replicates of 20 birds each: T1 - control; T2 - 0.1% CWSC; T3 - 500 ppb of ochratoxin; T4 - 0.01% CWSC + 500 ppb of ochratoxin. The parameters evaluated were feed intake; weight gain, feed conversion; relative weights of liver, kidneys and bursa of Fabricius. Ochratoxin in diet negatively affected (P > 0.05) the feed intake and weight gain when the birds were 21 and 42 days of age, and affected the feed conversion at 42 days of age. Was no interaction between CWSC and dietary ochratoxin. The CWSC improve the feed conversion of birds exposed or not to ochratoxin at 42 days of age. The ochratoxin or CWSC in diet did not affect the relative weight of organs evaluated. These results reflect that ochratoxin in the level used in diet impaired the feed intake, weight gain and feed conversion of the birds and the CWSC did not ameliorate these parameters in the presence of the ochratoxin.